Physician's manual on malnutrition - Florentino, Rodolfo F.;Solon, Florentino S. (Makati City, Philippines : Nutrition Center of the Philippines, 1977)
The presence of malnutrition as a major health problem points out the need to pursue concerted efforts towards the prevention and management of this crippling disorder.
Chapter 1. Nutrition and community health -- Chapter 2. Epidemiology, pathogenesis, and assessment of malnutrition -- Chapter 3. Protein - energy malnutrition -- Chapter 4. Vitamin deficiencies -- Chapter 5. Mineral deficiences -- Chapter 6. Medical management management of the severely malnourished -- Chapter 7. Dietary management of the severely malnourished -- Chapter 8. Assessment of recovery -- Chapter 9. Preventive health care -- Chapter 10. Surveillance.
Includes bibliographical references.
Keywords: MALNUTRITION